Spiritual and ideological foundations of nomadic statehood in historical studies (Journal of history-rus, 2022)
The article presents a historiographical analysis of the spiritual and ideological foundations of the nomadic state, which is a complex and internally structured political phenomena. Statehood is an indicator of the development and property of society, but at the same time it is also its ideology, political, social and cultural orientation, guiding the protection and development of the state. Modern historical thought is determined by new theoretical and conceptual approaches, the rejection of stereotypical views, taking into account alternative points of view and conceptual provisions. The analysis of the spiritual and ideological foundations of nomadic statehood is connected with the development of research principles, general historical processes, systemic approaches and new methodology. In the context of solving this problem, questions were raised and the main approaches were identified in solving further typological constructions of the theory of “nomadic statehood” on the basis of an interdisciplinary synthesis and civilizational discourse of modern historical science. An analysis of a large complex of historiographical sources shows that the mobility, dynamism of political processes in nomadic societies led to instability and mobility of the entire structure, and cardinal changes led to the transformation of the entire system as a whole. To increase the efficiency of theoretical and methodological research, it is necessary to continue studying the spiritual and ideological foundations of the institutions for managing nomadic structures, the integration of different types and models of power into a single imperial system. Key words: ideology, statehood, power, charisma, empire, nomads, scientific paradigms.